Romanian GPs Involvement in Caring for the Mental Health Problems of the Elderly Population: A Cross-Sectional Study - Sfetcu, Raluca; Toma, Daciana; Tudose, Catalina; Vladescu, Cristian (Frontiers in Neurology, 2021)
The mental health of the elderly is a matter of increased concern in the context of an aging population since currently only a small fraction of this population is receiving adequate care. The provision of treatment in primary care by the General Practitioners (GPs) has been proposed for over a decade as a potential solution, as services offered by GPs are more accessible, less susceptible to stigma, and have a more comprehensive view of the other health care problems that the elderly might suffer from. In this study, we explored the perception of Romanian GPs regarding their practice and roles in caring for the mental health of the elderly as well as the willingness to increase their future involvement in the management of dementia and other mental health problems. Data was collected via an online questionnaire structured on four dimensions: (1) GPs’ sociodemographic profile and practice characteristics, (2) GPs assessment of the services available for elderly with mental health problems, (3) GPs current involvement in mental health care for different categories of problems, and (4) factors that might influence the future involvement of GPs in providing care for elderly with mental health problems. The survey was sent via the member mailing lists of the National Society for Family Medicine. Results show that GPs are currently limited by prescribing possibilities, available resources and knowledge in the area, but they are willing to expand their role in the areas of early recognition and prevention of mental health problems as well as providing disease management and collaborative care. An improved communication with mental health care professionals, a better access to resources and having more financial incentives are the three most important categories for GPs to increase their involvement. In conclusion, increasing the access to personal and professional resources and setting up functional communication channels with specialized mental health care could motivate GPs to provide timely mental health support to elderly patients.